STRATEGI KOMUNIKASI PEMASARAN DINAS KEBUDAYAAN DALAM MEMPERKENALKAN FESTIVAL KETOPRAK DOR SEBAGAI KEARIFAN LOKAL KOTA MEDAN - Prietsawenny Riris T Simamora; Elok Perwirawati; Daniel Parulian Sihombing (JURNAL SOCIAL OPINION: Jurnal Ilmiah Ilmu Komunikasi, 2019)
This study aims at discussing the marketing communication strategy used by Department of Culture in introducing the Dor Ketoprak Festival as a local wisdom in Medan and implementing the marketing communication strategy in introducing the Dor Ketoprak Festival. Technique of collecting the data used is field research using obsertvation and interview method. Data analysis was done by qualitative research approach. Research findings show that there was a lack of preparedness in the planning and implementation, which still seems to lack data and coordination with the Ketoprak Dor group, it is not done yet a training has not been made to the Ketoprak Dor artists, as well as not yet approaching and establishing good relationships and cooperation with related parties such as the executive, private parties, the press, and others to strive to further introduce ketoprak art and culture to the general public and tourists in particular.